2013
DOI: 10.1021/jf404046v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium Oxide Nanoparticles on the Quality of Rice (Oryza sativa L.) Grains

Abstract: Despite the remarkable number of publications on the interaction of engineered nanoparticles (ENPs) with plants, knowledge of the implications of ENPs in the nutritional value of food crops is still limited. This research was performed to study the quality of rice grains harvested from plants grown in soil treated with cerium oxide nanoparticles (nCeO2). Three rice varieties (high, medium, and low amylose) were cultivated to full maturity in soil amended with nCeO2 at 0 and 500 mg kg(-1) soil. Ce accumulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(138 citation statements)
references
References 63 publications
14
123
1
Order By: Relevance
“…Rico et al showed that nCeO 2 decreased some of the nutrients in rice grains, including Fe, S, prolamin, glutelin, lauric and valeric acids, and starch. Moreover, nCeO 2 decreased the antioxidant properties of the rice grains (Rico et al, 2013). Our previous study (Zhao et al, 2014) also showed that ZnO NPs and CeO 2 NPs at certain doses induced sugar, starch, and protein content alterations in cucumber fruits.…”
Section: Introductionmentioning
confidence: 75%
“…Rico et al showed that nCeO 2 decreased some of the nutrients in rice grains, including Fe, S, prolamin, glutelin, lauric and valeric acids, and starch. Moreover, nCeO 2 decreased the antioxidant properties of the rice grains (Rico et al, 2013). Our previous study (Zhao et al, 2014) also showed that ZnO NPs and CeO 2 NPs at certain doses induced sugar, starch, and protein content alterations in cucumber fruits.…”
Section: Introductionmentioning
confidence: 75%
“…Previous reports revealed differences in Ce uptake in grains. For example, medium and low amylose rice varieties stored more Ce (1912 and 1853 μg kg −1 ) than high amylose variety (224 μg kg −1 ) when exposed to nCeO 2 -H treatment (Rico et al 2013b). On the contrary, wheat grown in control to nCeO 2 -H treatments did not show significant differences in Ce accumulations in grains (155-263 μg kg −1 ) .…”
Section: Cerium Accumulation In Leaves and Grainsmentioning
confidence: 99%
“…It was reported that Oryza sativa grains harvested from nano CeO 2 exposed plants had lower content of Fe, S, prolamin, glutelin, lauric and valeric acids, and starch (Rico et al, 2013b). In a similar exposure setting, nano CeO 2 decreased the Mo concentration in Cucumis sativus fruit and also altered nonreducing sugars, phenolic content and fractionation of proteins .…”
Section: Impact On Agronomic and Yield Characteristicsmentioning
confidence: 90%
“…For example, fatty acid content in Oryza sativa roots was significantly altered by nano CeO 2 treatments (Rico et al, 2013b). Plant lignin content was also reduced with increasing nano CeO 2 dosage, likely due to the fact that the balance between peroxidase activity and H 2 O 2 content has a regulatory role in lignin synthesis (Rico et al, 2013a).…”
Section: Oxidative Stress and Antioxidant Enzymesmentioning
confidence: 99%